The remediation of extremely acidic and moderate pH soil leachates containing Cu (II) and Cd (II) by native periphytic biofilm. (20th September 2017) - Wu, Yonghong; Yang, Jiali; Tang, Jun; Kerr, Philip; Wong, Po Keung
Abstract: The acidic washing process is a commonly applied approach to extract heavy metals (e.g. Cu and Cd) from soils. It is difficult, however, to purify the subsequent acidic soil leachates containing heavy metals. In this study, we proposed using ubiquitous native periphytic biofilm to clean soil leachates containing high concentrations of Cu (II) and Cd (II) under extreme and moderate acidic conditions. Results showed that the high concentrations of Cu (II) and Cd (II) present in the soil leachates after being washed with the eluents, water and mixed acidic solution (MAS), display average removal ratios by periphytic biofilm of 80.5 and 65.7% for Cu (II), and 42.9 and 68.6% for Cd (II), respectively. The sustainably grown periphytic biofilm acclimated to the extremely acidic (∼3.0) and moderate (∼7.1–8.0) pH soil leachates with Cu (II) and Cd (II) via self-adjustment of the microbial community structure and carbon metabolic potential. In the MAS system, the inclusion of mine tailings containing CaO neutralized the extreme pH conditions. Our results suggest that using native periphytic biofilm is a promising and clean approach to remediate extremely acidic and moderate pH soil leachates containing Cu (II) and Cd (II). Graphical abstract: